Microstrip Patch Antenna Development at K Band for Satellite Communication - R. Arivarasu; N. Ramabasi Reddy; K. Madhavi; A. Niranjan (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
A four-band microstrip patch antenna is designed to work for satellite applications. Out of four bands, one of the bands has a wide band width up to 8 GHz. These microstrip patch antennas can work in the allocated range of 10–40 GHz. The antenna designed can have low return losses and positive gain, which indicates that it can work for practical applications. The designed antenna added stubs on all three corner sides of the microstrip patch antenna for impedance matching. The design used for VSAT applications is the ANSYS HFSS R21. The HFSS (high-frequency structure simulator) software used for analysis of beamwidth, return losses, voltage standing wave ratio (VSWR), gain, gain polar plot, and 3D gain plot has been evaluated and is going to be verified. The gain of the antenna is very high, up to 8.25 dB when compared to the previous design, which was 3.25 dB higher.
Keywords: VSAT; HFSS; Beamwidth; k/Ku/ka band; VSAT Applications